SANCTUARY IN THE MARKETPLACE: COMMUNICATING RELIGIOSITY AND POP CULTURE IN THE PHILIPPINES - Edwin F Lineses (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2014)
Filipinos love to mall and it is no surprise that malls, being business enterprises, proliferate the country because of consumer demands. Malls provide various goods and services in one-stop-shop, including religious celebrations, to draw most people from all walks of life to this cycle of consumerism. The celebrations of mass often become shrouded with tinge of commercialism. It is in this context that a study, using indigenous methods and techniques of ethnography, of the mass-going culture of Filipinos inside the mall is vital in understanding an emergent language and culture of religiosity. It unravels the meaning of the celebration of the Eucharist in the mall from the vantage point of parishioners. This paper proposes an explanation for attending mass in the mall over regular parishes, which is the domain of religious profession. The paper argues that mall provided a sanctuary, a consecrated place of worship, even in the midst of a marketplace.